Numerical simulation of shock wave amplification in a bubble cluster on a supercomputer - Vshivkov, V.A.; Korneev, V.D.; Lazareva, G.G. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2007)
A parallel program is developed for simulation of plane-shock wave interaction with an axial bubble cylinder. The evolution of a bubble medium is described by a system of gas dynamics equations and by the Raleigh equation for a single gas bubble. A detailed analysis of the bubble cluster domain decomposition is given. The main parameters of the parallel algorithm are discussed. One of the results of supercomputer simulations is the dependence of the shock wave amplitude on the cluster radius.